The women's health little book of exercises four weeks to a leaner, sexier, healthier you! - Campbell, Adam (Rodale, 2014)
Based on the wildly successful Women's Health Big Book of exercises, this portable handbook offers readers step-by-step instructions (and color photos) on how to perfectly execute the best fat-torching, muscle-toning exercises ever choreographed. This essential workout guide is for any woman-from beginner to expert-who wants to lose weight fast, build strength, and tone those terrible trouble spots, namely the belly, butt, and thighs.Complete with fast, effective workouts for home use or to take to the gym, this easy-to-tote package gives readers access to their favorite routines wherever they go